Asset Lantung : Wara-Wara Akuntabilitas dan Ghost shopping dengan Pendekatan Netnografi - Alfiyatul Qomariyah; Sultan Syah; Sri Rahayu Syah (InFestasi, 2023)
Accountability is based on the need for an individual or entity to be able to express their anger over any day-to-day currency actions, decisions, or ex-penses that relate to them. Recognition is essential in the context of oil as-sets and natural resources to ensure that proper management and utiliza-tion are carried out. The study aims to provide an understanding of an ac-countability practice for managing Lantung assets (natural resource assets). This research uses an interpretive paradigm and qualitative method with Combination of Literature Study and Netnography Approaches. The re-sults of the study provide an understanding of accountability practices in-dicating that companies take various steps to secure their position from var-ious threats while maintaining their "power" The ghost shopping strategy by companies has yielded results in the pricing of Lantung. The interpreta-tion of agency theory as an accountability performance drama seeks to pre-sent capitalist values to the audience to remain focused on the appearance of accountability presented through financial statements (accounting prod-ucts). Finally, the values of capital (again) give legitimacy to decision-makers to stand on these capitalist values.